Conversions: gender and religious change in early modern Europe - Ditchfield, Simon; Smith, Helen (Manchester Shakespeare collection, 2017)
A timely and coherent collection on conversion studies of the Early Modern period, considering themes of conversion, materiality, embodiment and early modern spaces across and beyond Europe